CARD11 blockade suppresses murine collagen-induced arthritis via inhibiting CARD11/Bcl10 assembly and T helper type 17 response. (9th April 2014) - Wang, H; Zhao, J; Zhang, H; Huang, Y; Wang, S; Tu, Q; Yang, N
Summary: The scaffold protein caspase recruitment domain-containing protein 11 (CARD11) is implicated in the regulation of inflammation and autoimmunity. The present study aimed to explore the role of CARD11 in the pathogenesis of rheumatoid arthritis (RA). Mice with collagen-induced arthritis (CIA) were treated with either CARD11-targeted interfering RNA (CARD11 siRNA) or control siRNA by intraperitoneal injection every 3 days after CIA establishment. The clinical score of arthritis was recorded every other day. Synovial inflammation and cartilage erosion were evaluated by histology and microcomputed tomography (micro-CT). Serum anti-type II collagen (anti-CII) antibodies and cytokines were measured by enzyme-linked immunosorbent assay (ELISA). The CARD11/Bcl10 formation and nuclear factor-kappa B (NF-κB) activation was assessed by immunoprecipitation and immunoblotting, and the percentage of T helper type 17 (Th17) cells was determined by flow cytometry. Systemic administration of CARD11 siRNA significantly reduced the clinical score of CIA severity. As indicated by the histology, joint inflammation and destruction were attenuated by CARD11 siRNA treatment. Micro-CT demonstrated less severe joint destruction in CARD11 siRNA-treated mice than in control mice. CARD11 siRNA treatment resulted in inhibition of CARD11/Bcl10 formation and the subsequent NF-κB activation. In addition, treatment with CARD11 siRNA resulted in a pronounced decrease in proinflammatory cytokines interleukin (IL)-1β, IL-6 and IL-17. Serum anti-CII antibody and the percentage of Th17 cells were also significantly reduced. CARD11 is involved in the pathogenesis of CIA by formation of the CARD11/Bcl10 complex and enhancement of the Th17 cell response. Targeting CARD11 provides a novel research direction in the development of therapeutic strategies for RA.